2015
DOI: 10.1016/j.toxlet.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Povidone iodine skin absorption: An ex-vivo study

Abstract: Povidone iodine is a water-soluble complex used to disinfect the skin surface and it exerts prolonged germicidal action against a broad spectrum of germs. Indeed, it is often applied on burned skin, large wounds, deep tissues or mucosa. Notably some surgical hand-scrub solutions, which are considered safe antiseptics, contain large amounts of iodine that can be absorbed by skin. The aim of present study was to study the skin absorption of iodine after the application on the skin of povidone-iodine solution, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…In the only quantitative in vitro study to specifically measure iodine flux across a human epithelial membrane, the protocol included an infinite dose regime, saturation of the complete surface area of the experimental membrane, and exposure time of 24 hours. 59 They concluded that 10% PVP-I applied to human skin demonstrated a maximum ''iodine'' medium flux of 0.73 mg/cm 2 per hour. However, based on the limitations of the study, this conclusion cannot be utilized as evidence based.…”
Section: Povidone-iodine General Safetymentioning
confidence: 99%
“…In the only quantitative in vitro study to specifically measure iodine flux across a human epithelial membrane, the protocol included an infinite dose regime, saturation of the complete surface area of the experimental membrane, and exposure time of 24 hours. 59 They concluded that 10% PVP-I applied to human skin demonstrated a maximum ''iodine'' medium flux of 0.73 mg/cm 2 per hour. However, based on the limitations of the study, this conclusion cannot be utilized as evidence based.…”
Section: Povidone-iodine General Safetymentioning
confidence: 99%
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [7...…”
Section: Uncited Referencesunclassified
“…1 was repeated but after 10 minutes from the application, the nicotine donor solutions were removed and the skin surfaces were rinsed three times with 3.0 mL of milliQ water. Then, 1 mL of physiological solution was added to each donor chamber, in order to maintain the skin in the same hydration conditions of the experiment I and of the blank cells (Larese et al, 2008;Nesvadbova et al, 2015). The washing solutions were collected for following analysis.…”
Section: Experiments IImentioning
confidence: 99%